Feather teaching and training based on Kinect sensor and gesture recognition technology - Luoluo Zhang; Pin Zhong (Systems and Soft Computing)
With the development of information technology, the depth camera represented by Kinect can better help people obtain the relevant features of human movement, but the angle of data acquisition by a single Kinect device is relatively limited. There is inevitably occlusion. Therefore, this paper innovatively proposes a physical education teaching method based on multi-sensor equipment and posture recognition technology. The badminton teaching auxiliary training system is designed from bone information collection and fusion, bone point coordinate angle feature extraction, and badminton action classification and recognition. The auxiliary training system scientifically and standardly completes action training from three parts: badminton learning, action collection, and action evaluation. The results showed that the recognition algorithm proposed in this study better achieved joint angle conversion, with estimation error less than observation error. The matching accuracy in badminton standard motion analysis exceeded 90 %, and the error in slapping action was less than 0.01, which had good robustness. Trainers' athletic performance, agility and reaction speed have all improved. The research can enrich and innovate badminton teaching and training content, as well as provide effective reference and guidance for related physical education teaching.